Ungerechte Könige: Überlegungen zum Verhältnis von ethischen und politischen Begründungen in der antiken Philosophie - Brüllmann, Philipp (Begründen und Erklären im antiken Denken, 2025)
Abstract: “Unjust Kings: Some Reflections on the Relation between Ethical and Political Arguments in Ancient Philosophy.” According to the standard picture, ancient political philosophy is an ethical, eudaimonist project that aims to realize happiness and virtue in a state. This picture, though in general correct, needs to be modified. For there are questions of ancient political philosophy that seem to require a non-eudaimonist treatment. The aim of my paper is to both defend and explicate this claim. In order to do so, I take a look at Plato’s discussions of two kings: Archelaus of Macedon in the Gorgias and Temenos of Argos in Book III of the Laws. These kings share a number of interesting features, for both are described as unjust, irrational and egoistic. But they are considered, as I argue, from different perspectives. Archelaus is considered from an ethical, eudaimonist perspective. Plato refers to his character to bring out the link between happiness and virtue. Temenos, by contrast, is considered from a specifically political perspective. His character is supposed to explain why Argos, unlike Sparta, has perished. So, although in both cases, the king’s being unjust, irrational, and egoistic plays a key role within the argument, this argument follows different lines. This is most obvious in the case of the king’s egoism. Whereas the discussion of Archelaus’ egoism is shaped by the contrast between true and apparent self-interest, the discussion of Temenos’ egoism is marked by the contrast between pursuing one’s own interests and doing the right thing or acting in the interest of others. This conceptual shift, which is also connected to the Laws’ interest in non-ideal circumstances, drives a wedge between normative considerations (what is required from a king qua king) and considerations of self-interest. It thus severs the link that is most characteristic for eudaimonist explanations. The political question why Argos has perished requires a non-eudaimonist treatment.